Prevalence and Risk Factors of Delirium and Subsyndromal Delirium in Older Adults - Faiqa Nasir, Shehrbano Batool, Anam Nasir, Muhammad Faisal Bacha, Aysha Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Delirium is the most prevalent geriatric issue that is independently associated with poor outcomes in terms of discharge, length of hospital stay, and increased mortality. Subsyndromal delirium (SSD) is defined by the presence of delirium symptoms that do not yet meet the definition of full-blown delirium. The present study aimed to determine the incidence and delirium-related risk factors in older adults. Method: This prospective study was conducted on 420 elderly patients (>60 years) in the Department of Medicine of Benazir Bhutto Hospital Rawalpindi and Liaquat University Medical and Health Sciences, Jamshoro Hyderabad, from April 2021 to December 2021. Study protocol was approved from research and ethical committees of the institutions. The purpose of the study was explained to the participants after taking written informed consent. Patients were classified into three categories are as follows: delirium, subsyndromal delirium, and cases without both delirium and subsyndromal delirium. Detailed history taking, comprehensive geriatric assessment, and clinical examination from each individual were recorded. All the collected data were analyzed using SPSS version 26. Results: Of the total 420 elderly patients, the incidence of delirium and subsyndromal delirium was 96 (22.9%) and 72 (17.1%) respectively. There were 264 (62.9%) male and 156 (37.1%) females. The overall mean age was 68.4± 4.8 years. Delirium and subsyndromal delirium cases were distributed based on the patient’s age were as follows: 62 (64.6%) and 42 (58.3%) in 60-70 years, 24 (25%) and 22 (30.6%) in 71-80 years, and 10 (10.4%) and 8 (11.1%) in >81 year. Of the 96 delirium cases, the incidence of hypoactive type, hyperactive type, and mixed type was 54 (56.3%), 18 (18.8%), and 24 (24.9%) respectively. Based on cognitive assessment, about 36 (8.6%) MMSE score <23, 78 (18.6%) had MMSE score <18, and 54 (12.9%) did not respond to MMSE. The incidence of common comorbidities such as hypertension, chronic liver disease, asthma, ischemic heart disease, cerebrovascular disease, diabetes, and malignancy was 144 (34.3%), 82 (19.5%), 26 (6.2%), 120 (28.6%), 24 (5.7%), 184 (43.8%), and 14 (3.3%) respectively. Conclusion: The present study found that the incidence of delirium and subsyndromal delirium was 22.9% and 17.1% respectively. Adverse outcomes such as increase in length of hospital stay, mortality, and discharge are independently associated with delirium. Efforts to prevent disease may identify patients who require clinical attention. Keywords: Delirium, subsyndromal delirium, risk factors